2022
DOI: 10.1016/j.jcmg.2021.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance for Patients With COVID-19

Abstract: COVID-19 is associated with myocardial injury caused by ischemia, inflammation, or myocarditis. Cardiovascular magnetic resonance (CMR) is the noninvasive reference standard for cardiac function, structure, and tissue composition. CMR is a potentially valuable diagnostic tool in patients with COVID-19 presenting with myocardial injury and evidence of cardiac dysfunction. Although COVID-19–related myocarditis is likely infrequent, COVID-19–related cardiovascular histopathology findings have been reported in up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 75 publications
7
91
0
6
Order By: Relevance
“…In symptomatic patients, CMR is the most sensitive method to exclude ischemia and preexisting cardiomyopathies 106 while confirming cardiac changes due to SARS-CoV-2 infection, including myocardial inflammation, nonischemic epicardial scar, and pericardial effusion/enhancement, all of which are demonstrable after 4 weeks. 106 , 107 For patients who are unstable or exhibit high-risk features (eg, hypotension, ventricular arrhythmias), evaluation at an advanced heart failure center is recommended. Endomyocardial biopsy should be considered in those with clinical deterioration, particularly if heart block or ventricular arrhythmias are present and obstructive coronary artery disease has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In symptomatic patients, CMR is the most sensitive method to exclude ischemia and preexisting cardiomyopathies 106 while confirming cardiac changes due to SARS-CoV-2 infection, including myocardial inflammation, nonischemic epicardial scar, and pericardial effusion/enhancement, all of which are demonstrable after 4 weeks. 106 , 107 For patients who are unstable or exhibit high-risk features (eg, hypotension, ventricular arrhythmias), evaluation at an advanced heart failure center is recommended. Endomyocardial biopsy should be considered in those with clinical deterioration, particularly if heart block or ventricular arrhythmias are present and obstructive coronary artery disease has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, reports of myocardial damage in association with COVID-19 comprise acute ischemic injury (type 1 myocardial infarction) [58], along with non-ischemic injury (i.e., myocarditis) [59,60], stress cardiomyopathy [61], heart failure (HF) [62] and secondary cardiac injury caused by sepsis and critical illness [63] (Figures 1 and 2). Mechanisms of myocardial injury may be indirect via systemic inflammatory response or direct (viral infection, thought to be less common) [64]. Specifically, autopsy studies on 39 COVID-19 patients identified virus in the heart tissue of 62.5% of patients [65].…”
Section: Cardiovascular Involvementmentioning
confidence: 99%
“…Palpitations and chest pain are the most common subjective findings [9]. A study by Frankfurt University Hospital revealed that 78% of survivors of COVID-19 had CV alterations, and 60% of them still showed signs of persistent myocardial inflammation Mechanisms of myocardial injury may be indirect via systemic inflammatory response or direct (viral infection, thought to be less common) [64]. Specifically, autopsy studies on 39 COVID-19 patients identified virus in the heart tissue of 62.5% of patients [65].…”
Section: Cardiovascular Involvementmentioning
confidence: 99%
“…In addition, it can be attributed to sepsis or exacerbation of preexisting chronic conditions such as cardiomyopathy. [ 4 , 5 ] Of note, more than one etiology may coexist in the same patient. A complex interplay of multiple mechanisms appears to underlie COVID-19-mediated myocardial injury.…”
mentioning
confidence: 99%
“… [5] CMR is a highly sensitive diagnostic tool in evaluating COVID-19-associated myocardial involvement findings such as inflammation, late gadolinium enhancement, nonischemic epicardial scar, and pericardial effusion. [ 4 , 5 ]…”
mentioning
confidence: 99%